(In) Acessibilidade na web para pessoas com deficiência visual: um estudo de usuários à luz da Cognição situada - Janicy Aparecida Pereira Rocha (2013)
This research is characterized as a user study guided by social approach. The guiding objective was to understand how people with congenital and acquired blindness interact with the Web and how they perceive their (in)accessibility, in order to identify the needs and contributions of Web Content Accessibility Guidelines WCAG 2.0 to build websites as appropriate as possible to that user's profile. The Situated Cognition was adopted as theoretical support, because it is based on the view that human actions are adapted to the situation and to the context, influenced by its various dimensions (individual, social, motivational, emotional). The option of conducting research with users with visual impairment is justified by the importance of the Internet in their lives and the many barriers they still find while accessing the Web. Considering the scope and objectives of the research, a qualitative study was carried out with eight users, selected from the snowball sampling. Data were collected through semi-structured interviews and interaction tests in natural environment. The research results show that the participants had their first contact with the Internet and the Web from different forms and motivations, this process is permeated by various emotions, prevailing the positive ones. The speeches of the participants show that the perception of the (in) accessibility is influenced by several factors: the user agents, the target audience of the website, usability problems, violation of accessibility recommendations and knowledge and experience in the use of both the Internet/Web, as the user agents. In relation to the factors that influence the behavior and actions of users during access mediated by screen readers, it was noticed: the physical and digital environment, the resources and additional programs that they use, flexibility and improvisation based on their past experience, their needs and motivations to access and use and the visual memories and concepts they have. It could be observed that positive emotions arise on accessibility and negative emotions emerge of inaccessibility. It was verified the importance of the websites being developed in accordance with WCAG, but it was noticed also that they need some additions. Moreover, it was demonstrated that its important to understand the specificities and demands of users with visual disabilities so that websites become increasingly accessible and inclusive.